PENILAIAN BISNIS PERUSAHAAN PT. GARUDA INDONESIA (PERSERO) Tbk TERHADAP LAPORAN KEUANGAN TAHUN 2017 SAMPAI DENGAN TAHUN 2020 - Muhammad Rosidi, rosidi (Jurnal Publikasi Ekonomi dan Akuntansi, 2022)
ABSTRACT The purpose of making this research journal is to conduct a business assessment of PT Garuda Indonesia (Persero) Tbk, namely evaluating and measuring the level of financial health of PT Garuda Indonesia (Persero) Tbk with indicators of liquidity ratios, solvency, activity and profitability. The research method used is library research, namely by studying relevant data from various sources. The author uses secondary data in the form of financial statements for 2017 to 2020. The analytical model used in this research is Cash Ratio, Current Ratio, Inventory Turnover, TATO, Collections Periods, ROE, ROI and Total Own Capital to Total Assets. Financial data is taken from the financial statements of PT Garuda Indonesia (Persero) Tbk in the form of Income Statement and Balance Sheet. The level of health is measured based on the Decree of the Minister of SOE No.Kep 100/MBU/2002 where PT Garuda Indonesia (Persero) Tbk is included in the Non-Infrastructure SOE. The results of this study indicate the indicator has decreased every year. So it can be concluded that PT Garuda Indonesia (Persero) Tbk has Unhealthy business and financial performance with CCC predicate in 2017 to 2019 and CC predicate in 2020.